2000
DOI: 10.1177/155005940003100311
|View full text |Cite
|
Sign up to set email alerts
|

Early-latency Somatosensory Evoked Potentials Elicited by Electrical Acupuncture after Needling Acupoint LI-4

Abstract: The stimulating methods of prior studies on somatosensory evoked potentials (SEPs) elicited by acupoint stimulus had involved surface electrodes, while the clinical practice of acupuncture is mostly performed by inserting the acupuncture needle inside the body. Clinical observations show that there are often some special sensations when LI-4 is needled. To observe if the SEPs produced by acupoint acupuncture had a distinguishing property, we studied the SEPs elicited by electrical acupuncture after the acupunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Acupuncture suppresses the amplitude and the latencies of somatosensory evoked potentials (SEP) (Xu et al, 1993) and differences in amplitude and latencies of the SEPs between acupuncture and control points have been demonstrated (Wei et al, 2000). Regarding the electroencephalogram (EEG), some investigators reported an increase in the EEG power in all frequency bands after acupuncture (Tanaka et al, 2002;Xu et al, 1998), while others failed to show an effect (Rosted et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture suppresses the amplitude and the latencies of somatosensory evoked potentials (SEP) (Xu et al, 1993) and differences in amplitude and latencies of the SEPs between acupuncture and control points have been demonstrated (Wei et al, 2000). Regarding the electroencephalogram (EEG), some investigators reported an increase in the EEG power in all frequency bands after acupuncture (Tanaka et al, 2002;Xu et al, 1998), while others failed to show an effect (Rosted et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study confirmed the previous findings that acupuncture in a specific manner can significantly change cerebral EEG parameters as shown by different authors. 9,27 In parallel with ␣1 increase during VA, LI4-stimulation led to more pronounced pain-sensation compared to PA, as well as more incidents of specific de qi sensations, which are a part of the concept of acupuncture. The fact that pain and de qi sensations occurred also in some volunteers during PA might be explained by activation of nociceptors during needle pressure at the skin or by expectation in sense of a placebo effect.…”
mentioning
confidence: 96%
“…The objective of Dr Chen ZH's [4] group is to study the effects of electro-acupuncture on electroencephalography in vascular dementia (VD) patients. According to the Hasegawa dementia scale (HDS), the 46 VD patients were classified into three grades and divided into the EA group and the nimotop group randomly.…”
Section: Development Of Acupuncture-reading With Eeg Mri and Petmentioning
confidence: 99%